1999
DOI: 10.1074/jbc.274.10.6797
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Function Analysis of the UDP-N-acetyl-d-galactosamine:PolypeptideN-acetylgalactosaminyltransferase

Abstract: Mucin-type O-glycosylation is initiated by a family of UDP-GalNAc:polypeptide N-acetylgalactosaminyltransferases (ppGaNTases). Based on sequence relationships with divergent proteins, the ppGaNTases can be subdivided into three putative domains: each putative domain contains a characteristic sequence motif. The 112-amino acid glycosyltransferase 1 (GT1) motif represents the first half of the catalytic unit and contains a short aspartate-any residue-histidine (DXH) or aspartate-any residue-aspartate (DXD)-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
81
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(87 citation statements)
references
References 33 publications
4
81
0
2
Order By: Relevance
“…Previous experiments involving site-specific mutagenesis of selected conserved residues confirmed that mutations in the catalytic domain eliminated catalytic activity. In contrast, mutations in the lectin domain had no or only little effects on catalytic activity of at least one GalNAc-transferase isoform, GalNAc-T1 (14). However, recent evidence demonstrates that some GalNAc-transferases in vitro exhibit unique activities with partially GalNAc-glycosylated glycopeptides.…”
mentioning
confidence: 91%
See 3 more Smart Citations
“…Previous experiments involving site-specific mutagenesis of selected conserved residues confirmed that mutations in the catalytic domain eliminated catalytic activity. In contrast, mutations in the lectin domain had no or only little effects on catalytic activity of at least one GalNAc-transferase isoform, GalNAc-T1 (14). However, recent evidence demonstrates that some GalNAc-transferases in vitro exhibit unique activities with partially GalNAc-glycosylated glycopeptides.…”
mentioning
confidence: 91%
“…However, it is conceivable that GalNAc glycosylation of Ser 20 precedes Thr 14 , and that initial attachment of GalNAc at Ser 20 indeed induces GalNAc-T4 to utilize Thr 14 . Surprisingly, GalNAc transfer to Ser 10 in -VTSA-with the GalNAc 2 TAP25 (TAPPAHGV T*S 10 APDTRPAPGST*APPA) substrate was poor compared with GalNAc 4 TAP24.…”
Section: Galnac-t4 Transfer To At Least Three Sites In the Muc1mentioning
confidence: 99%
See 2 more Smart Citations
“…Structural studies on a number of enzymes have shown that these aspartate residues coordinate the Mn 2ϩ ion that plays a central role in catalysis (31)(32)(33)(34). Moreover, the aspartates have been shown to necessary for the activity of a wide range of glycosyltransferases (29,(35)(36)(37)(38). In this paper we determine the stoichiometry of Mnn9p and Van1p in M-Pol I, and use mutations in their DXD motifs to investigate in vivo and in vitro the contribution the two proteins make to the activity of the complex.…”
mentioning
confidence: 99%